Comparison of Biogenic Amorphous Silicas Found in Common Horsetail and Oat Husk With Synthetic Amorphous Silicas - Lindner, Gottlieb Georg; Drexel, Claus-Peter; Sälzer, Katrin; Schuster, Tobias B.; Krueger, Nils (Frontiers in Public Health, 2022)
The present study summarizes the current literature on the presence and the structure of biogenic amorphous silica (BAS) in nature. Based on this review, it is shown that BAS is ubiquitous in nature and exhibits a structure that cannot be differentiated from the structure of synthetic amorphous silica (SAS). The structural similarity of BAS and SAS is further supported by our investigations—in particular, specific surface area (BET) and electron microscope techniques—on oat husk and common horsetail. Many food products containing BAS are considered to be beneficial to health. In the context of the use of SAS in specific applications (e.g., food, feed, and cosmetics), this is of particular interest for discussions of the safety of these uses.